Pricing When Customers Have Limited Attention - Boyacı, Tamer; Akçay, Yalçın (Management Science, 2018)
We study the optimal pricing problem of a monopolistic firm facing customers with limited attention and capability to process information about the value (quality) of a single offered product. We model customer choice based on the theory of rational inattention in the economics literature, which enables us to capture not only the impact of true quality and price, but also the intricate effects of customer’s prior beliefs and cost of information acquisition and processing. We formulate the firm’s price optimization problem assuming that the firm can also use the price to signal the quality of the product to customers. To delineate the economic incentives of the firm, we first characterize the pricing and revenue implications of customer’s limited attention without signaling, and then use these results to explore perfect Bayesian equilibria of the strategic pricing signaling game. As an extension, we consider heterogeneous customers with different information costs as well as prior beliefs. We discuss the managerial implications of our key findings and prescribe insights regarding information provision and product positioning. This paper was accepted by Gad Allon, operations management.